Complex Chromosomal Rearrangements in B-Cell Lymphoma: Evidence of Chromoanagenesis? A Case Report - Ortega, Veronica (Neoplasia, 2016)
Genomic instability is a well-known hallmark of cancer. Recent genome sequencing studies have led to the identification of novel phenomena called chromothripsis and chromoanasynthesis in which complex genomic rearrangements are thought to be derived from a single catastrophic event rather than by several incremental steps. A new term chromoanagenesis or chromosomal rebirth was coined recently to group these two one-step catastrophic events together. These phenomena suggest an evolutionary modality for cancer cells to circumvent individual mutational events with one simultaneous shattering of chromosomes resulting in the random reassembling of segmented genetic material to form complex derivative chromosomes. We report a case of possible chromoanagenesis in a patient with diffuse large B-cell lymphoma. Chromosome analysis from the biopsy showed a complex karyotype with multiple numerical and structural rearrangements including a translocation of chromosomes 3 and 7 involving the BCL6 gene region, with the derivative chromosome further rearranging with chromosomes 14, 7, and 22 with involvement of the IGH gene region. Fluorescence in situ hybridization studies confirmed these findings. Chromosomal microarray studies showed multiple complex copy number variations including a chromosome 12 abnormality, the complexity of which appears to suggest the phenomenon of chromoanagenesis. Our case further illustrates that lymphomagenesis can be complex and may arise from a catastrophic event resulting in multiple complex chromosome rearrangements.